PREFERENCE OF PUBLIC SECTOR AND PRIVATE SECTOR MUTUAL FUNDS BY THE WOMEN INVESTORS – A STUDY WITH SPECIAL REFERENCE TO COIMBATORE CITY - Gopika . S. S, Dr. K. Amutha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
An essential part of savings is the expectation of returns. But return is always an uncertain factor. It depends upon the future. In general sense, savings and investment are different. Savings means the total amount earned by the investor whether invested or not. Investment means a portion of savings sacrificed by the investor to achieve the returns. At the macro level or at the individual level, the values of investment or savings can be evaluated using different statistical techniques. For investing funds, one must have a deep or thorough knowledge about the opportunities available in the market. There is a need for knowledge and information about the process of investment, risk and return to have a good and sound portfolio. . If investments are made through proper planning, an investor can earn a regular and stable income and thereby gets a relief from taxation. For the developing countries like India, Brazil etc. there are inflationary trends i.e. rising prices. The main problem caused by rise in prices is falling the standard of living of individuals. A right choice of investment helps to overcome the inflationary forces. Before making investment, one should evaluate different investment options available and must compare the rate of return of different investment to overcome the inflation